The implementation of UTAUT 2 model in predicting customer behavior - Ines Hafizhah Zain; Perengki Susanto (Operations Management and Information System Studies, 2022)
The purpose of this study was to examine: Application of the UTAUT 2 model for predicting behavioral intention and use behavior of digital payment DANA. The sample used in this study was 272 samples with the criteria of the people of the city of Padang, and using digital payment DANA, the sampling technique was purposive sampling. The research was analyzed using SEM analysis with SmartPLS version 3.7 software. The results of this study were: that performance expectancy, hedonic motivation, price value, and habit all have a positive and significant effect on behavioral intention. Effort expectancy has no significant positive effect on behavioral intention. Social effect and facilitating conditions have a positive effect but no significant on behavioral intention. Behavioral intention, facilitating condition, and habit have a positive and significant effect on user behavior.